Comparing Network Performance of Mobile VoIP Solutions - Dantas, Rafael (Electronic Communications of the EASST, 2018)
Maintaining consistent VoIP quality is a challenging task, especially where it is carried using a mobile internet connection. With greater than 50% of the world's mobile user population using older GSM incarnations, this is very much a present technical research challenge. his paper presents an approach to improving mobile VoIP telephony by drastically lowering the bandwidth consumption while maintaining acceptable call quality when compared to competitor solutions. Although initial test had good results, we've found that a detailed experiment might be necessary to benefits of the implementation.